DC/TMD axis I subtyping: generational and gender variations among East Asian TMD patients - Adrian Ujin Yap; Chengge Liu; Jie Lei; Ji Woon Park; Seong Hae Kim; Byeong-min Lee; Kai Yuan Fu (BMC Oral Health, 2023)
Abstract Objectives This study examined the generational-gender distinctions in Diagnostic Criteria for Temporomandibular disorders (DC/TMD) subtypes among East Asian patients. Methods Consecutive “first-visit” TMD patients presenting at two university-based TMD/orofacial pain clinics in China and South Korea were enlisted. Demographic information along with symptom history was gathered and clinical examinations were performed according to the DC/TMD methodology. Axis I physical diagnoses were rendered with the DC/TMD algorithms and categorized into painful and non-painful TMDs. Patients were categorized into three birth cohorts, specifically Gen X, Y, and Z (born 1965–1980, 1981–1999, and 2000–2012 respectively) and the two genders. Data were evaluated using Chi-square/Kruskal-Wallis plus post-hoc tests and logistic regression analyses (α = 0.05). Results Gen X, Y, and Z formed 17.2%, 62.1%, and 20.7% of the 1717 eligible patients examined (mean age 29.7 ± 10.6 years; 75.7% women). Significant differences in prevalences of arthralgia, myalgia, headache (Gen X ≥ Y > Z), and disc displacements (Gen Z > Y > X) were observed among the three generations. Gen Z had substantially fewer pain-related and more intra-articular conditions than the other generations. Women presented a significantly greater frequency of degenerative joint disease and number of intra-articular conditions than men. After controlling for generation-gender interactions, multivariate analyses showed that “being Gen X” and female increased the risk of painful TMDs (OR = 2.20) and reduced the odds of non-painful TMDs (OR = 0.46). Conclusions Generational-gender diversities in DC/TMD subtypes exist and are important for guiding TMD care and future research endeavors.